1995
DOI: 10.1111/j.1365-2109.1995.tb00940.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatfall of pearl oyster, Pteria sterna (Gould), on experimental collectors at Bahía de La Paz, South Baja California, Mexico

Abstract: Spatfall of pearl oyster, Pteria sterna (Gould), was analysed at two sites, stations Gaviota and Merito, at Bahía de La Paz, South Baja California, Mexico, during an annual cycle in 1991‐1992. and from surface to 15 m depth. Sampling was carried out monthly using experimental collectors which remained immersed for 60‐65 days. Four different substrates were tested for spat settlement preference: a native bush called ‘chivato’, dry palm leaves, and red and yellow plastic onion bags: temporal variations, and hori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
4
11
0
2
Order By: Relevance
“…The general pattern resembles the winter–spring recruitment season described for the species in La Paz, Baja California Sur (Cáceres‐Martínez et al . ; Monteforte, Kappelman‐Piña & Lopez‐Espinosa ; Cáceres‐Puig ). In the southern portion of the Gulf of California, P. sterna is characterized by continuous gametogenesis throughout the year, with winter and spring spawning peaks (Díaz & Buckle‐Ramírez ; Saucedo & Monteforte ; Vite‐García & Saucedo ).…”
Section: Discussionmentioning
confidence: 99%
“…The general pattern resembles the winter–spring recruitment season described for the species in La Paz, Baja California Sur (Cáceres‐Martínez et al . ; Monteforte, Kappelman‐Piña & Lopez‐Espinosa ; Cáceres‐Puig ). In the southern portion of the Gulf of California, P. sterna is characterized by continuous gametogenesis throughout the year, with winter and spring spawning peaks (Díaz & Buckle‐Ramírez ; Saucedo & Monteforte ; Vite‐García & Saucedo ).…”
Section: Discussionmentioning
confidence: 99%
“…They also pointed out the necessity to further study the stock density and cleaning effects on P. mazatlantica. However, for Pinctada mazatlantica, as well as for Pteria sterna, preliminary studies indicated that the collectors should be recovered not later than 3 months after immersion, otherwise high seed mortality can occur as a result of predation and competition among associated species (Monteforte and Garcia-Gasca, 1994;Monteforte and Wright, 1994;Monteforte et al, 1995;Wright, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, there are several studies with Pteria sterna (Gould, 1851) and Pinctada mazatlantica (Hanley, 1846) (Monteforte and Cariño, 1992;Monteforte and Garcýa-Gasca, 1994;Monteforte and Wright, 1994;Monteforte, et al, 1995;Monteforte et al, 1996;Monteforte and Morales-Mulia, 2000). Pinctada imbricata (Roding, 1758) is studied in Venezuela, Colombia (Borrero, 1994;Pico et al, 1999), andAustralia (O'Connor andLawler, 2004), showing good culture potential.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, spat remain in the collectors for as long as 6 months after which they are removed and placed into different kinds of rearing containers where the culture process takes place until the time of pearl induction operations (Wada 1973;Coeroli et al 1984;Gervis & Sims 1992). However, for P. mazatlanica, as well as for P. sterna, earlier works have demonstrated that collectors must be recovered no later than 3 months after immersion, otherwise high mortality of spat can arise as a result of predation and competition with associated species (Monteforte & Garcõ Âa-Gasca 1994;Monteforte & Wright 1994;Monteforte, Kappelman & Espinoza 1995;Wright 1997). Because the harvested spat is still small and fragile, the nursery culture constitutes a well-de®ned stage in the culture process of our local pearl oyster species.…”
Section: Discussionmentioning
confidence: 99%